Confucian conception of critical thinking in teaching English as a foreign language in Myanmar - Soe Darli Wai (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The Confucian-Western dichotomy often interprets as Eastern and Western learning. In the framework of lifelong learning, the Confucian philosophy hypothesizes learning as a lifelong progression through which learners of any age learn to become an honorable person and to lead a morally outstanding life. This research has been done to find out whether the Confucian conception of critical thinking possesses is like harmonizing mechanisms to those of the Western conception of critical thinking. This research discovers the comparison of Confucian conception of critical thinking and the Western conception of critical thinking through literature review and text analysis. Reflection on interview survey, questionnaire survey and classroom observation show that Confucian “enlightening approach” works efficiently in today’s effort in critical thinking cultivation in English teaching. The study suggests detailed research in building the theoretical framework for the Confucian conception of critical thinking, examination of other approaches to develop critical thinking abilities in addition the “enlightening approach,” and in-depth studies of present practical research on critical thinking in TEFL in Myanmar to see how they can be useful in materializing Confucian conception of critical thinking.